Preparation of pancreatic mRNA: cell-free translation of an insulin-immunoreactive polypeptide. - Lomedico, P T (1976)
Total nucleic acid extraction and selection of poly A-containing molecules yield preparative quantities of undegraded mRNA from adult and fetal pancreas. Using a stringent immunoassay, this mRNA is found to direct the synthesis of an immunoreactive insulin polypeptide in the wheat germ translation system. On sodium dodecyl sulfate polyacrylamide gels, this polypeptide (12,000-13,000 daltons) is larger than proinsulin (9,000 daltons).